The influence of a liner on deep bulk-fill restorations: Randomized clinical trial - Torres, Carlos Rocha Gomes [UNESP]; Mailart, Mariane Cintra [UNESP]; Rocha, Rafael Santos [UNESP]; Sellan, Pablo Lenin Benitez [UNESP]; Contreras, Sheila Célia Mondragón [UNESP]; Di Nicoló, Rebeca [UNESP]; Borges, Alessandra Bühler [UNESP] (Elsevier, 2020)
Objective: The aim of this study was to evaluate the influence of a liner on the clinical performance of deep posterior restorations performed with bulk-fill composite. Methods: 30 subjects received two restorations on deep preparations in posterior teeth, without pulpal exposure, after selective carious-tissue removal in one-stage. The internal walls reached the inner quarter of dentin, but with a radiographically detectable zone of firm dentin remaining. The pulpal protection using a layer of glass ionomer composite liner (Ionoseal, Voco) was applied in just one preparation. The adhesive system Futurabond U (Voco) was applied in all preparations, which were restored with the bulk-fill pure Ormocer nanohybrid composite (Admira Fusion Xtra - Voco), in up to 4 mm thick increments. All restorations were evaluated using the FDI criteria after 7 days, 6, 12 and 24 months postoperatively. Results: After 24-months, 25 patients attended the recall and 50 restorations were evaluated. The Fisher's statistical analysis (5%) showed no difference between the techniques for the esthetic, functional and biological properties. No postoperative sensitivity was reported for both groups. Conclusion: The application of a liner did not influence the clinical performance of deep restorations with bulk-fill Ormocer composite. Clinical relevance: The application of a liner with a GIC-based material did not have a significant effect on the clinical performance of bulk-fill restorations and seems to be unnecessary for the material tested.
Keywords: Bulk-fill; Glass ionomer cement; Liner; Ormocer; Pulp Protection